Method for improving consistency of inter-node contact resistance of fuel cell stack

By controlling the freeze-out cycle temperature and number, the fuel cell stack is activated and load-loaded purged, and the contact state between the new replacement membrane electrode and the bipolar plate is optimized, which solves the problem of inconsistent contact resistance distribution after the fuel cell stack repair and replacement, and significantly improves performance and durability.

CN119581606APending Publication Date: 2025-03-07SUNRISE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411705189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

After the fuel cell stack repair and replacement, the contact resistance distribution between the new and old membrane electrodes and the bipolar plate is inconsistent, resulting in a decrease in performance and durability.

Method used

By controlling the freeze-excavation cycle temperature and number, the fuel cell stack is activated and load-loaded purged, the contact state between the new replacement membrane electrode and the bipolar plate is optimized, and the consistency of the contact resistance distribution is improved.

Benefits of technology

It effectively improves the difference in contact resistance distribution between new and old batteries, greatly reduces the standard deviation of contact resistance, and improves the performance and durability of fuel cell stacks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581606A_ABST
    Figure CN119581606A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the consistency of contact resistance between sections of a fuel cell stack, which comprises the following steps: activating the fuel cell stack after section change, carrying out on-load purging on the cathode side and the anode side of the cell by using air and hydrogen after activation, placing the stack in a high-low temperature test box after purging, and carrying out freezing cycle, so as to improve the consistency of the contact resistance between the sections of the fuel cell stack. And quick matching of the new and old batteries is completed after multiple freezing cycles. According to the method, the change of the assembly force of the stack is adjusted by controlling the freezing cycle temperature, the contact state between a new membrane electrode and a bipolar plate is improved by utilizing the repeated change of the assembly force in the stack in the freezing cycle process of the fuel cell stack, the contact resistance between interfaces is reduced, and the distribution consistency of the contact resistance between new and old cells of the fuel cell stack is improved. The method effectively solves the problem of large contact resistance difference between the new and old membrane electrodes and the bipolar plate after maintenance and section replacement of the high-power fuel cell stack, and rapidly improves the matching state between the new membrane electrode and the bipolar plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for improving the consistency of inter-node contact resistance after node replacement in a fuel cell stack. Background Art

[0002] Fuel cells are highly efficient and green energy conversion devices. The only byproducts of the reaction are water and heat. They are an ideal power source and have received extensive attention in the automotive field in recent years. With the continuous advancement of technology and the increase in market demand, fuel cells are rapidly developing in the direction of high power. For a 100-kilowatt-class stack, the number of cells is as many as hundreds. In the long-term operation process, it is inevitable that several or dozens of cells will have performance degradation too fast and need to be replaced.

[0003] The assembly force of a fuel cell stack can generally reach 20-30KN, and the gas diffusion layer is a porous material. After the assembly is completed and operated for a period of time, it will produce a large plastic deformation. This leads to a large difference in the matching between the newly replaced membrane electrode and the original membrane electrode and the bipolar plate during the maintenance of the fuel cell stack. This difference is mainly reflected in the contact resistance of the single section, that is, the contact resistance between the newly replaced membrane electrode and the bipolar plate is large, which will cause the single cell where the newly replaced membrane electrode is located to have a larger ohmic resistance and higher heat generation when the fuel cell is running at a high electrical density point, affecting its performance and durability. Generally speaking, after the fuel cell stack is repaired, due to the large plastic deformation of the original membrane electrode, in order to prevent overpressure, the assembly force will be reduced during reassembly, which further aggravates the matching problem between the newly replaced membrane electrode and the bipolar plate. Increasing the assembly force to improve the contact state between the newly replaced membrane electrode and the bipolar plate will cause severe overpressure in the edge section or other unreplaced sections and damage the membrane electrode structure. Therefore, the matching between the new and old membrane electrodes and bipolar plates after the fuel cell stack is an engineering practical problem that needs to be solved urgently.

[0004] The patent title in the prior art: "A method for optimizing the contact resistance distribution of fuel cells" proposes a method for optimizing the contact resistance distribution using finite element analysis. This method achieves the target contact resistivity distribution optimization through the key assembly interface morphology design, avoiding the problem of excessively high battery assembly structure space and weight ratio caused by the traditional method of increasing the end plate thickness, and can effectively improve the space utilization of fuel cells and reduce the ohmic loss of fuel cells. However, this method mainly improves the consistency of contact resistance distribution by optimizing the main parameters in the early stage of fuel cell stack design from the perspective of stack design, but lacks effective means to improve the problem of poor consistency of contact resistance distribution after fuel cell stack maintenance and replacement.

[0005] The patent title in the prior art: "A method for repairing a hydrogen fuel cell stack" proposes a device and method for rapid repair of a fuel cell stack, which includes an inspection table, a carrying device, a clamping device, a limit mechanism and a bottom detection device. The device can sequentially inspect the circuit board, cardboard and conductive film of the battery stack through the carrying device, the clamping device, etc., and inspect the performance of each battery cell assembly through the bottom detection device, so as to realize rapid inspection and repair of the fuel cell stack. However, this method mainly builds repair equipment and proposes a rapid repair method to address the problem that the current fuel cell stack lacks conventional repair means and key repair equipment, but does not propose an effective solution to the problem of poor consistency in contact resistance distribution after the fuel cell stack is repaired and replaced. Summary of the invention

[0006] In view of the problems existing in the prior art, the present application proposes a method for optimizing the contact state by controlling the temperature and number of freeze-thaw cycles to solve the problem of the lack of effective improvement of the contact resistance difference between the new and old membrane electrodes and bipolar plates after the fuel cell stack is replaced. The method utilizes the temperature-dependent characteristics of the fuel cell stack's own materials to improve the stress changes inside the fuel cell, thereby improving the contact state between the membrane electrode and the bipolar plate and improving the consistency of the contact resistance distribution. The specific scheme includes:

[0007] Activate the fuel cell stack after the section replacement;

[0008] Air and hydrogen are introduced into the fuel cell stack for on-load purge to remove water generated by the reaction inside the cell;

[0009] The fuel cell stack is placed in a high and low temperature test chamber for freeze-thaw cycles to optimize the contact state between the newly replaced membrane electrode and the bipolar plate.

[0010] By controlling the number of freeze-thaw cycles and the freeze-thaw temperature, the changes in the internal assembly force of the fuel cell stack can be indirectly controlled to achieve repeated self-regulation of the assembly force.

[0011] Furthermore, the specific process of activating the fuel cell stack includes: placing the fuel cell on a test platform for activation, introducing air with a humidity range of 50%-100%, a stoichiometric ratio range of 1.5-2.0, and a back pressure range of 50-100kPa; introducing hydrogen is pressure-controlled, the hydrogen-air pressure difference range is 10-40kPa, a reflux humidification method is used on the hydrogen side, the activation current density range is 800mA / cm2-1600mA / cm2, and each activation time range is 20-30min.

[0012] Furthermore, dry air is introduced into the cathode side of the fuel cell stack with a metering ratio of 2-2.5, the gas volume corresponds to a density range of 600-900mA / cm2, and the back pressure range is 40-80kPa. Dry hydrogen is introduced into the anode side, and the hydrogen side is pressure controlled with a hydrogen-air pressure difference range of 10-20kPa. A current of 10-20A is applied during the purge process, and the system is shut down after purging to a given voltage.

[0013] Furthermore, the purged fuel cell is placed in a high and low temperature test chamber, and the freeze-thaw cycle temperature of the test chamber is set to -30°C to 40°C, the number of cycles is 3, and the test is completed after the freeze-thaw cycle is completed.

[0014] The method for improving the consistency of contact resistance distribution after the replacement of the fuel cell stack proposed by the present invention is simple and practical, and can effectively improve the problem of large differences in contact resistance distribution between new and old batteries. The method uses air and hydrogen to purge the cathode side and the anode side of the replaced fuel cell stack with load after activation, and performs a freeze-thaw cycle test after purging. On the one hand, the volume change of the residual liquid water in the membrane electrode during the freezing cycle process is used to quickly open the mass transfer channel and accelerate the activation speed of the newly replaced membrane electrode. On the other hand, the contact state between the newly replaced membrane electrode and the bipolar plate is improved by controlling the freeze-thaw cycle temperature and number, and the contact resistance distribution consistency of the whole stack is improved. The method disclosed by the present invention does not require any adjustment to the stack assembly process, and the contact state between the newly replaced membrane electrode and the bipolar plate can be optimized by controlling the freeze-thaw cycle temperature and number. Compared with the method of adjusting the contact state by increasing the assembly force, the method in the present application can avoid the problem of local overpressure of the edge node and overpressure of some unreplaced nodes caused by applying the assembly force. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0016] Figure 1 A schematic diagram of ohmic resistance of different sections of a fuel cell stack before section replacement in the present invention;

[0017] Figure 2 This is a schematic diagram of the ohmic resistance distribution after the section is replaced in the present invention;

[0018] Figure 3 It is a schematic diagram of the ohmic resistance distribution of different nodes after the contact resistance is optimized by the method of the present invention;

[0019] Figure 4It is a schematic diagram of the change of the standard deviation of internal resistance before the joint replacement, after the joint replacement (before optimization) and after the joint replacement (after optimization) in the present invention;

[0020] Figure 5 This is a schematic diagram of the change in internal resistance of different sections of the fuel cell stack after section replacement before and after running for 72 hours. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0022] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0023] The present invention discloses a method for improving the consistency of contact resistance between nodes of a fuel cell stack. The method belongs to the field of fuel cell technology and mainly includes the following contents: activating the fuel cell stack after node replacement, and after activation, using air and hydrogen to purge the cathode side and anode side of the battery with load, and after the purge is completed, placing the stack in a high and low temperature test box for freeze-thaw cycle, and completing the rapid matching of new and old batteries after several freeze-thaw cycles. The method adjusts the change of the stack assembly force by controlling the freezing cycle temperature, and utilizes the repeated changes of the internal assembly force of the stack during the freeze-thaw cycle of the fuel cell stack to improve the contact state between the new membrane electrode and the bipolar plate, reduce the contact resistance between the interfaces, and improve the consistency of the contact resistance distribution between the new and old batteries in the fuel cell stack. The method effectively solves the problem of large difference in contact resistance between the new and old membrane electrodes and bipolar plates after the maintenance and node replacement of a high-power fuel cell stack, and quickly improves the matching state between the new membrane electrode and the bipolar plate.

[0024] from Figure 1 It can be seen from the figure that the ohmic resistance of each battery cell in the fuel cell stack is relatively small before the cell is replaced, and the ohmic resistance of the edge cell is slightly smaller than that of the middle cell. Figure 2 It can be seen that the cells in Sections 1, 155 and 370 were replaced. After the fuel cell stack was repaired and replaced, the ohmic resistance increased to varying degrees, but the changes in Sections 1, 155 and 370, which were replaced with new membrane electrodes, were more significant.

[0025] Table 1 shows the variation of ohmic resistance of different sections before and after section replacement.

[0026] Table 1 Changes in ohmic resistance of different sections before and after section replacement

[0027]

[0028] It can be seen from Table 1 that after the stack is repaired and replaced, the ohmic resistance of the single cell with a new membrane electrode increases by more than 50%, among which the first section changes most significantly, increasing by about 84.2%, and the single cell without a replaced membrane electrode increases by about 14%-30%. The ohmic resistance distribution of the fuel cell stack after the replacement of the section is optimized by the method described in this application. Figure 3 shown. Figure 3 It can be seen that the overall contact resistance of the fuel cell stack is reduced after optimization using the method described in this patent, among which the contact resistance of a single cell with a new membrane electrode changes more significantly.

[0029] Table 2 shows the changes in ohmic resistance of different nodes before and after optimization using the method described in this patent.

[0030] Table 2 Changes in ohmic resistance of different nodes before and after optimization

[0031]

[0032] Figure 4 It can be seen that among the internal resistances of the 8 single cells monitored, the standard deviation of the fuel cell stack increased by about 3.1 times after the cell was replaced. After adopting the contact resistance optimization method described in this patent, the standard deviation was reduced to the level before the cell was replaced. That is, the method described in this patent can increase the standard deviation of the contact resistance of the fuel cell stack after the cell was replaced by more than 3 times.

[0033] Figure 5 It can be seen that the conventional activation method cannot change the contact resistance of the fuel cell, and the internal resistance of different sections does not change significantly before and after activation.

[0034] Example 1: This example takes a high-power metal bipolar plate stack in actual engineering applications as the research object, with a membrane electrode effective area of ​​298 cm2, a metal bipolar plate, a corrugated flow field, and 370 stack sections.

[0035] 1. Battery activation: Place the fuel cell on the test platform, and let in air with a relative humidity of 60%, a stoichiometric ratio of 2.0, and a back pressure of 100kpa; hydrogen pressure control, hydrogen-air pressure difference of 20kpa, use hydrogen reflux humidification method, activation electric density point of 1000mA / cm2, activate for 1h and then stop for 0.5h, and perform activation three times;

[0036] 2. Stable operation: Run for 24 hours at 1000mA / cm2 electric density point, and stop for 1 hour every 4 hours to make the contact resistance of the fuel cell stack stable;

[0037] 3. Single cell impedance test: The high frequency impedance of the fuel cell stack sections 1, 2, 3, 155, 157, 368, 369 and 370 is tested at 800mA / cm2. The test results are as follows: Figure 1 shown.

[0038] Comparative Example 1:

[0039] 1. Replacement of fuel cell stack sections: Replacement of membrane electrodes in sections 1, 155 and 370 of the fuel cell stack;

[0040] 2. Battery activation: Activate according to step 1 described in Example 1;

[0041] 3. Stable operation: Perform a stable operation test according to step 2 described in Example 1;

[0042] 4. Single cell impedance test: Perform single cell impedance test according to step 3 described in Example 1.

[0043] Comparative Example 1 Single Cell Impedance Test Results Figure 2 As shown in the figure, it can be seen that the battery ohmic resistance increases significantly after the battery is replaced.

[0044] Comparative Example 2:

[0045] 1. Battery activation: The battery stack after the replacement is activated according to step 1 described in Example 1;

[0046] 2. Full operation: refer to step 2 shown in Example 1 to conduct a full operation test, the operating conditions are the same as in Example 1, and the total operating time is 72 hours;

[0047] 3. Single cell impedance test: Perform single cell impedance test according to step 3 of Example 1. The test results are as follows: Figure 5 As shown. It can be seen that after full operation, the battery ohmic internal resistance has no obvious change;

[0048] Comparative Example 3:

[0049] 1. Battery activation: same as in Example 1;

[0050] 2. Shutdown purge: dry air is introduced into the cathode side of the fuel cell, with a gas flow rate of 3660L / min and a back pressure of 40kpa. Dry hydrogen is introduced into the anode side, with pressure control and a hydrogen-air pressure difference of 20kpa. A current of 20A is applied during the purge process until the average voltage of the stack is 0.75v.

[0051] 3. Freeze-thaw cycle: Set the low temperature operating temperature of the low temperature box to -30℃, the operating time to 12h, the high temperature operating temperature to 40℃, the operating time to 6h, and the number of cycles to 3 times;

[0052] 4. Battery activation: After the freeze-thaw cycle is completed, activation is performed according to Example 1;

[0053] 5. Single cell impedance test: Perform single cell impedance test according to step 3 of Example 1. The test results are as follows: Figure 3 As shown in the figure, it can be seen that the contact resistance is significantly improved after adopting this method.

[0054] Through the test results of the above embodiments and comparative examples, it can be found that after the fuel cell stack is repaired and replaced, the ohmic internal resistance of the newly replaced section and the unreplaced section battery increases accordingly. This is mainly related to the change in the matching state between the membrane electrode and the bipolar plate before and after disassembly. However, the ohmic internal resistance of the battery with the newly replaced membrane electrode increases more significantly, indicating that its contact state changes more. After fully activating and operating it, the ohmic internal resistance does not change substantially. After optimization using the method described in this patent, it can be seen from the test results of Comparative Example 3 that the ohmic internal resistance of the unreplaced section can be reduced by more than 10%, and the ohmic internal resistance of the newly replaced section can be reduced by more than 30%.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for improving the consistency of internode contact resistance of a fuel cell stack, characterized in that: include: Activate the fuel cell stack after the section replacement; Air and hydrogen are introduced into the fuel cell stack for on-load purge to remove water generated by the reaction inside the cell; The fuel cell stack is placed in a high and low temperature test chamber for freeze-thaw cycles to optimize the contact state between the newly replaced membrane electrode and the bipolar plate.

2. A method for improving the consistency of internode contact resistance of a fuel cell stack according to claim 1, characterized in that: By controlling the number of freeze-thaw cycles and the freeze-thaw temperature, the changes in the internal assembly force of the fuel cell stack can be indirectly controlled to achieve repeated self-regulation of the assembly force.

3. A method for improving the consistency of inter-node contact resistance of a fuel cell stack according to claim 1, characterized in that: The specific process of activating the fuel cell stack includes: placing the fuel cell on a test platform for activation, introducing air with a humidity range of 50%-100%, a stoichiometric ratio range of 1.5-2.0, and a back pressure range of 50-100kpa; introducing hydrogen with pressure control, a hydrogen-air pressure difference range of 10-40kpa, a reflux humidification method on the hydrogen side, an activation current density range of 800mA / cm2-1600mA / cm2, and an activation time range of 20-30min each time.

4. A method for improving the consistency of internode contact resistance of a fuel cell stack according to claim 1 or 2, characterized in that: Dry air is introduced into the cathode side of the fuel cell stack with a metering ratio of 2-2.

5. The gas volume corresponds to a density range of 600-900mA / cm2 and a back pressure range of 40-80kpa. Dry hydrogen is introduced into the anode side. The hydrogen side is pressure controlled with a hydrogen-air pressure difference range of 10-20kpa. A current of 10-20A is applied during the purge process, and the system is shut down after purging to a given voltage.

5. A method for improving the consistency of internode contact resistance of a fuel cell stack according to claim 1 or 3, characterized in that: The purged fuel cell is placed in a high and low temperature test chamber, and the freeze-thaw cycle temperature of the test chamber is set to -30°C ~ 40°C, the number of cycles is 3 times, and the test is completed after the freeze-thaw cycle is completed.